Innovation and change in professional practice: a case study - Williamson, Vicki Kay (Curtin University, 1999)
This study reports research about innovation and change in the professional practice of the staff at the Library and Information Service (LIS) staff at Curtin University of Technology, Perth, in Western Australia. The historical context of the study is Australian higher education and university libraries in the early 1990s. It reports, examines and analyzes key events and activities of the LIS staff strategic planning process both as an educational innovation and a driver of change in professional practice. The investigation of educational innovation and change is the object of the study, specifically the application of strategic planning.Literature from the 30-year history of writing and research about educational innovation and change is reviewed in terms of its relevance to the study. In addition, selected literature about organizational theory and strategic planning in libraries is presented. From this literature emerged the particular innovation and change framework, which guide the research.A justification for the selection of the particular research approach is explained and data collection, organization and analysis are described. The study uses official LIS corporate records as its primary source of data, supplemented by published materials to assist in the explanation of the particular circumstances of the LIS case.The results of the data analysis are presented in terms of the key events and activities of the LIS case. From this analysis conclusions are drawn in relation to the research questions which underpin the study and in terms of the component parts of the innovation and change framework. In particular, conclusions relate to the key organizational factors shaping the response to innovation; the characteristics of the context of change; key organizational processes helping to ensure successful adoption; the articulation of a shared vision and processes to ensure a shared vision. In relation to the innovation and change framework the change process is viewed as adoption dominated; as a move towards a learning organization; through the characteristics of the context of change and through other factors influencing change.Flowing from the research findings, recommendations are made for professional practice and further research.As a case study that reports, examines and analyses the complex dimensions of organizational change, the study is rich in detail and provides a real-life example of organizational and educational change.